Investigating Junior High School Students' Scientific Thinking Ability in Understanding Global Warming - Nur Rahmah; Mohammad Jamhari; Ratman; Sulastriani (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Science education in junior high school plays a crucial role in developing students' scientific thinking, particularly in understanding global issues like global warming. This study aims to assess the scientific thinking abilities of seventh-grade students at three state junior high schools in Palu City, using a descriptive approach and a test based on seven aspects of scientific thinking as defined by García-Carmona (2023). The findings reveal that approximately 80% of students showed progress in scientific thinking, with 12% achieving a competent level and 8% remaining in the beginner category. However, their understanding of scientific information from discourse and graphics averaged only 26%. Overall, students demonstrated developing scientific thinking skills, which could enhance their comprehension of scientific concepts, especially related to everyday experiences and environmental issues shared on social media. The role of teachers is essential in guiding students to understand and critically evaluate scientific information, such as articles on global warming. The study recommends developing interactive, problem-based teaching strategies to further improve students' scientific thinking skills. Future research should explore the role of media technology, teachers, and parents in supporting the development of scientific thinking regarding natural phenomena to advance science education in Palu and its surrounding areas.